Hubungan antara Citra Tubuh dengan Tingkat Kecemasan Ibu Masa Menopause di Kelurahan Awipari Kecamatan Cibeureum Kota Tasikmalaya - Endang Astiriyani; Yati Budiarti; Nuraini Hidayat (Jurnal Medika Cendikia, 2016)
Menopause is the time when menstrual periods stop permanently. In this moment, there is a decrease in hormone estrogen and it brings about the changes in physical which is followed the changes physiological of women. The minus acceptance of changes physical will cause the changes of behavior or the evaluation to physical which called body image. If the women has accept and love herself, then someone will safe and free from the anxiety. This research use analytic method and crossectional approach. The research site ini Awipari Village Cibeureum District Tasikmalaya City. The population of this research are all of women on menopause period which totaled 122 persons. The technique in taking sample is stratified proportional random sampling which totaled 93 respondents. Based on the result of the research that most of respondent’s body image on menopause period are in accept category which totaled 55 persons (59,1%) and most of women on menopause period have anxiety level in middle category which totaled 54 persons (58,1%). The conclusion of this research is there is relation between body image with the women’s anxiety level on menopause period in Awipari Village Cibeureum District Tasikmalaya City.